Efektivitas dan Peningkatan Sekolah Konteks Intelektual dan Kebijakan - Wiwik Wijayanti (Dinamika Pendidikan, 2011)
The fact   that  effectiveness research found  its ongtns  in the phenomenon  of  the  inefectiveness school. If school  were  really perfect, fulfilling  their missions to the great satisfaction on pupils, parents,  school board and politicians  at local and national level, nobody would ever have wanted  to  start  a process  of school  improvement with' teachers .through convicing them that improving their own performance is the right thing to do. School  effectiveness  needs a  diftnition.because the  concept  is  not altogether clear.  We cannot just  look at the output of the black box caledl 'school'; we also have to measure the input into it. Because we have to deal with    a  very complex  entity,  we  need indicators or factors  that  can  be compared and, even when we have school effectiveness factors,  it still  is difficult to know whether we are looking at causes or needs to be based on facts and figures derivedfrom a substantial number of school, which suggests the usually quantitative approach of school t;ffectiveness.   Keywords: Effectiveness, improvement